2017
DOI: 10.2196/jmir.7385
|View full text |Cite
|
Sign up to set email alerts
|

Activity Recognition for Persons With Stroke Using Mobile Phone Technology: Toward Improved Performance in a Home Setting

Abstract: BackgroundSmartphones contain sensors that measure movement-related data, making them promising tools for monitoring physical activity after a stroke. Activity recognition (AR) systems are typically trained on movement data from healthy individuals collected in a laboratory setting. However, movement patterns change after a stroke (eg, gait impairment), and activities may be performed differently at home than in a lab. Thus, it is important to validate AR for gait-impaired stroke patients in a home setting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 31 publications
1
80
1
Order By: Relevance
“…Nevertheless, we observed that the peak acceleration from real-world data exceeded the range of accelerations of the in-laboratory activities. This is not surprising because prior studies also found that in-laboratory activities look different from real-world unstructured behaviors [ 30 ]. Thus, falls and activity data during natural use of the phone must be collected to build a fall-detection system that can be deployed in an everyday scenario.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, we observed that the peak acceleration from real-world data exceeded the range of accelerations of the in-laboratory activities. This is not surprising because prior studies also found that in-laboratory activities look different from real-world unstructured behaviors [ 30 ]. Thus, falls and activity data during natural use of the phone must be collected to build a fall-detection system that can be deployed in an everyday scenario.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have generally used validation on non-amputee participants despite the fact that the clinical population is the real target. However, participants with mobility impairments display different movement patterns from unimpaired individuals, which can affect the accuracy of activity recognition classifiers [ 28 - 30 ]. We pursued the possibility that amputee movements during activities and simulated fall events may have been unique enough to suggest population-specific model training.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant when considering a system for real-world monitoring of PD. We have previously shown that models trained on activities performed in a lab do not always generalize to activities performed at home [37]. Though the study tasks were designed to approximate naturalistic behavior, it is still critical to validate the performance of the any symptom detection model during day-to-day activities in the community.…”
Section: Limitationsmentioning
confidence: 99%
“…One reason is that gait patterns in individuals with disabilities can be markedly different from those of able-bodied subjects [ 15 ], and the algorithms could use different sensor features to identify activities in different populations [ 9 , 29 ]. Indeed, former studies found that activity recognition models trained on a population of young able-bodied individuals generalize poorly to patient populations, such as the elderly or patients of stroke or Parkinson’s disease [ 9 , 11 - 13 ]. Our findings are in line with these results and show that additional variability can be introduced by the use of different KAFOs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of wearable- and mobile phone–based AR studies have been conducted using healthy individuals, whereas relatively fewer studies are focused on people with disabilities [ 6 ], such as those resulting from stroke [ 7 - 9 ] or Parkinson disease [ 10 , 11 ]. Some of these studies showed that a model trained on young healthy individuals will yield poor performance when used with a different population [ 9 , 11 - 13 ], including those who need an assistive device for walking [ 14 ]. These differences arise due to the fact that movements are unique to individuals, and movements in people with a disability are different from that of able-bodied individuals [ 15 ].…”
Section: Introductionmentioning
confidence: 99%